Secrets of the code the unauthorized guide to the mysteries behind the Da Vinci code - Burstein, Daniel (CDS Books, 2004)
Secrets of the Code, a five-month New York Times bestseller, is a sweeping tour, guided by renowned experts, through the many provocative ideas raised in The Da Vinci Code. With excerpts from many original works, all-new material, and interviews with prominent scholars exploring the novel’s underlying themes, Secrets of the Code will satisfy your curiosity, engage your imagination, and provide you with insights to better understand the historical and religious issues of the novel.